Dr. Thokozani Mhlambi and Dr. Katharina Fink on his project "Umgungundlovu Suite for Reed Ensemble" - Mhlambi, Thokozani; Fink, Katharina (Cluster Conversations, 2023)
Cluster fellow Dr. Thokozani Mhlambi talks with his host Dr. Katharina Fink about his life, his love for music, his artist fellowship in the Cluster and his latest project - a music-based story set in the ancient Zulu capital of Umgungundlovu.